Diffusion-reaction of nutrient in immobilized slab biocatalyst for first and zero order reactions - Jameel, Ahmed Tariq; R Muhamad Fakih, RM Syibli Milasi (IIUM Press, 2011)
The effect of nutrient diffusion on the overall reaction rate inside porous slab biocatalyst containing an immobilized enzyme or cells has been investigated theoretically. Zero-order and first-order kinetics were studied. The problem is represented in mathematical model developed using shell mass balance on the thin slab of biocatalyst. The second order differential equations developed for zero and first order kinetics are solved analytically to fInd the concentration profile inside the slab biocatalyst. The concentration profile is obtained as a function of Thiele modulus which in turn was used to evaluate effectiveness factor. From the analysis, high diffusion rate of substrate into the porous area increased the concentration profiles and effectiveness factor.